FEATURES OF THE FORMATION OF KAZAKH GRAMMATICAL TERMINOLOGY PRIOR TO A.BAITURSYNULY - Karbozova, Bulbul Davletkhanovna; Kambarova, Bekzat Gabitovna (SCIENCE and SOCIETY, 2026)
The article examines the prerequisites for the formation of Kazakh grammatical terminology in the early twentieth century and its historical-linguistic characteristics. The study analyzes the multivalence of terms, their multilayered linguistic nature, and orthographic instability in early Russian–Kazakh dictionaries and educational materials. It also explores the influence of the Arabic grammatical tradition, Russian missionary linguistics, and Jadid enlightenment on the development of Kazakh term formation. As a result, the period prior to Akhmet Baitursynuly is evaluated as a pre-theoretical and transitional stage in the development of Kazakh scientific terminology.